Intervention to Improve Mammography Screening at a Student-Run Free Clinic - DiLorenzo, Madeline A; Osterbur Badhey, Marika L; Roth, Lauren; Cohen-Levy, Wayne B; Badhey, Arvind K; Lin, Juan; Jordan, William B; Nosal, Sarah C; Cortijo, Amarilys; Schoenbaum, Ellie (Journal of Student-Run Clinics, 2019)
Background: Most late-stage breast cancer occurs in those who have never been screened. Uninsured women have lower screening rates than insured women. Student-run free clinics (SRFCs) caring for uninsured women can test interventions that attempt to increase screening rates. Methods: The United States Preventive Task Force guidelines were used to determine patient eligibility for screening mammography in a SRFC. Medical students began receiving education on screening mammography on May 31, 2013 while a simultaneous intervention to streamline workflow related to mammography referrals was implemented. We assessed the change in counseling and referral rates pre- and post-intervention as well as the impact of race/ethnicity, chronic disease status, and preferred language on the likelihood of getting counseled and referred for screening mammography. We also investigated the impact of the intervention on screening mammography attendance rates. Results: We collected data from the medical records of 106 women (171 patient visits) pre-intervention and 113 women (193 patient visits) post-intervention. The intervention significantly improved the rate of mammography counseling (from 54.4% to 81.9%) and mammography screening referrals (from 37.7% to 70.6%). Preferred language, race/ethnicity, and chronic disease status were not associated with counseling and referral rates. The intervention did not improve mammography attendance. Conclusions: An education and workflow intervention in a SRFC that improved counseling and referral rates did not improve mammography attendance. Further studies are needed to investigate patient-level barriers that may be affecting mammography appointment attendance.